Association of alcohol consumption with hypertension or prehypertension in Chinese adolescent: A cohort study of the China Health and Nutrition Survey - Meiqi Chen; Juan Liu; Menglin Fan; Bin Li; Yong Ren; Shaoyong Xu (The Journal of Clinical Hypertension, 2024)
Abstract This study was conducted to investigate the association between alcohol consumption in adolescence and the risk of hypertension or prehypertension development in early adulthood. This cohort study included adolescent participants aged 12–18 years from the 2000–2011 China Health and Nutrition Survey. Cox proportional risk regression models were used to analyze the associations of the frequency of alcohol consumption, alcohol intake, and type of alcohol with the risk of developing hypertension or prehypertension. Restricted cubic spline analysis was used to assess the dose–response relationships for alcohol intake and their hazard ratios (HRs). A total of 1556 participants were included in the final analysis. Among the overall population, 448 (30.81%) and 35 (34.31%) participants developed hypertension or prehypertension, respectively. Compared with no alcohol consumption, alcohol consumption ≥ 2 times/week and consumption of ≥2 types of alcohol were associated with an increased risk of hypertension and prehypertension, with HRs of 1.97 (95% confidence interval [CI] 1.17–3.34; p = 0.011) and 1.77 (95% CI 1.01–3.09; p = 0.046), respectively. Alcohol intake of > 96 mL/week was associated with an increased risk of hypertension and prehypertension, with HRs of 2.09 (95% CI 1.12–3.90; p = 0.020) and 2.07 (95% CI 1.11–3.84; p = 0.021), respectively. The restricted cubic spline analysis showed that the risk of developing high blood pressure or prehypertension tends to increase with increasing alcohol consumption. Heavy alcohol consumption in adolescence increased the risk of developing hypertension and prehypertension in early adulthood.